EGFR‐ERK pathway regulates CSN6 to contribute to PD‐L1 expression in glioblastoma. Issue 5 (5th March 2020) - Su, Lingrui; Guo, Wenli; Lou, Lei; Nie, Saisai; Zhang, Qing; Liu, Ying; Chang, Ying; Zhang, Xianghong; Li, Yuehong; Shen, Haitao
Abstract: Glioblastoma (GBM) is the most common and malignant brain tumor in adults. Recently, programmed death‐1/programmed death‐ligand 1 (PD‐1/PD‐L1) checkpoint blockades have been applied for GBM treatment. However, the mechanism of PD‐L1 upregulation in GBM is still unclear. COP9 signalosome 6 (CSN6) is crucial for maintaining the protein stabilization in cancer cells. In this study, we applied human GBM specimens and cell lines to investigate whether the EGFR‐ERK pathway regulates CSN6 for PD‐L1 upregulation. Data from The Cancer Genome Atlas dataset showed that high expression of EGFR, CSN6, and PD‐L1 in patients with glioma was associated with poor prognosis. In 47 human GBM specimens, high expression of PD‐L1 was associated with low amount of CD8 + T cell infiltration as well as the poor prognosis of patients. CSN6 was positively correlated with EGFR and PD‐L1 expression in human GBM specimens. We treated two GBM cell lines (U87 and U251) with epidermal growth factor (EGF) in vitro, and found EGF‐upregulated p ‐EGFR, p ‐ERK, CSN6, and PD‐L1 expression in GBM cells. PD98059, the ERK blocker, inhibited upregulations of CSN6 and PD‐L1 in EGF‐treated cells. Inhibition of CSN6 by small interfering RNA decreased PD‐L1 expression but also increased CHIP expression in GBM cells. When the cells were treated with EGF and cycloheximide (CHX), a protein synthesis inhibitor, EGF‐reduced CHX‐induced CSN6 and PD‐L1 turnover in GBM cells. Furthermore, CSN6‐mediated downregulation of PD‐L1 was inhibited by MG132, a proteasome inhibitor in U87 cells. Thus, these results suggest that the EGFR‐ERK pathway may upregulate CSN6, which may inhibit PD‐L1 degradation and subsequently maintain PD‐L1 stability in GBM.